Significant versus symbolic universes : sorting out the terminology - Van Dyk, P. J. (Journal for semitics, 2011)
It is argued that scholars of religion and anthropology should prevent falling victim to what is termed "the fallacy of assumed cosmology" by rather using different terms to describe phenomena within a magico-mythical cosmology (significant universe) as opposed to terms in a modern scientific cosmology (symbolic universe). The author therefore suggests that the terms signs, idols, images, icons, rituals, spells / enchantments, curses, blessings, customs, taboos and the concept of sacredness are restricted to a magico-mythical cosmology. In contrast terms such as symbol, statue, picture, ceremony, formula, habit, convention and respect should be reserved for the modern scientific cosmology and be avoided when describing phenomena from magico-mythical contexts such as the Old Testament, ancient texts and pre-scientific cultures.